Performance of a Domestic Refrigerator Using Nanoparticles-Based Polyolester Oil Lubricant - Haque, Muhammad E.; R. A., Bakar; K., Kadirgama; M. M., Noor; Shakaib, M. (Universiti Malaysia Pahang, Malaysia, 2016)
The performance of a domestic refrigerator with the addition of nanoparticles in the lubricant was experimentally investigated. Different sizes of nanoparticles of Al2O3 and TiO2 were added to the polyolester (POE) oil in two different volume concentrations (0.05 and 0.1 vol.%). Energy consumption tests and freeze capacity tests were then performed on the refrigerator. The investigation results showed that the refrigerator worked normally and safely with the nanolubricants. The results of the experiments indicated that the refrigerator performed better with nanolubricants as compared to pure POE oil. The COP of the systems was increased by 19% and 22% when 0.05% and 0.1% Al2O3 nanoparticles were added to the POE oil respectively. The system with 0.1% volume concentration of Al2O3 and TiO2 nanoparticles added to the POE oil consumed 27.73% and 14.19% less energy as compared to the pure POE oil system. Hence, this study showed that the addition of nanoparticles in the lubricant oil of the refrigerator is practical and it enhanced the performance of the refrigerator